PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PADA PT.SURACOJAYA ABADI MOTOR CABANG PINRANG - Astuti, Reski Sri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to describe the effect of capital structure on financial performance at PT. Suracojaya Abadi Motor Pinrang Branch. The data collection techniques used in this study are data collection techniques through company documents. For example, a brief history of the company, organizational structure, financial reports, and others. This research uses quantitative analysis which is implemented by using an analytical tool, namely multiple linear regression. The results of the study can be concluded that the capital structure does not affect the financial performance of PT. Suracojaya Abadi Motor Pinrang Branch.